2019
DOI: 10.1016/j.ijppaw.2018.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma madeirae sp. n.: A species of the clade T. cruzi associated with the neotropical common vampire bat Desmodus rotundus

Abstract: Molecular phylogenetic studies have revealed the growing diversity of bat trypanosomes. Here, 14 isolates from blood samples of the vampire bat Desmodus rotundus (Phyllostomidae) from Rio de Janeiro, Southeast Brazil, were cultivated, and morphologically and molecularly characterized. All isolates represent a novel species named Trypanosoma madeirae n. sp. positioned in the Neobat lineage of the clade T. cruzi. The Neobat lineage also comprises closely related trypanosomes of clades Neotropic 1, 2 and 3 from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…was associated with large male D. rotundus bats (Becker, Bergner, et al, ). Therefore, we propose that the unstructured distribution of Bartonella genotypes may stem from the flow of male bats carrying Bartonella spp., in a process similar to that was hypothetized for Trypanosoma madeirae (Barros, Lima, Schubach, & Teixeira, ).…”
Section: Discussionmentioning
confidence: 71%
“…was associated with large male D. rotundus bats (Becker, Bergner, et al, ). Therefore, we propose that the unstructured distribution of Bartonella genotypes may stem from the flow of male bats carrying Bartonella spp., in a process similar to that was hypothetized for Trypanosoma madeirae (Barros, Lima, Schubach, & Teixeira, ).…”
Section: Discussionmentioning
confidence: 71%
“…The three isolates of T. dionisii investigated (M1011, M1014, and M1015) were obtained in a study in different municipalities of Rio de Janeiro, where 22 samples of trypanosomatids were isolated by hemoculture of 84 bats [ 32 ]. Three samples were characterized as T. dionisii and 19 as T. madeirae [ 33 ]. Interestingly, we observed that T. dionisii and T. madeirae [ 33 ] were present in the same colony and were infecting the same bat species, Desmodus rotundus (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Three samples were characterized as T. dionisii and 19 as T. madeirae [ 33 ]. Interestingly, we observed that T. dionisii and T. madeirae [ 33 ] were present in the same colony and were infecting the same bat species, Desmodus rotundus (data not shown). However, although co-infection is common among bats in nature, it was not detected in this study, probably because the isolation and amplification methods used for the culture of parasites exert a selective force, owing to which mixed infections are not frequently detected.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to bugs, sand flies that bite bats have been implicated as trypanosome vectors, with Trypanosoma pessoai believed to be transmitted by Dipteran sp. [ 69 ]. It has been speculated that the T. pessoai flagellates detected in Phlebotomus vespertilionis are transmitted to the vertebrate host via contamination in superficial skin lesions or bite wounds, given the absence of metacyclic trypanosomes detected in the anterior station of the insect [ 107 ].…”
Section: Bat Trypanosomesmentioning
confidence: 99%